The periodic table: contest and exhibition - Silva, Aurora (2006)
The systemization and organization of ideas and concepts is an integral part of science. In chemistry, the organization of the periodic table of the chemical elements in the 1860s was one of the greatest scientific breakthroughs ever made and in fact during the 20th century it became a universally recognized scientific icon (1). The periodic table is the fundamental classificatory scheme of the elements and summarizes the realm of chemistry (2). Simply knowing the position of an element in the periodic table tells us about its properties and is usually enough to predict how the element will behave in a wide variety of different situations or reactions (1). Based on this potential mine of information, it is possible to make reliable predictions of the properties of the compounds that each element forms. Nowadays, the concept of the periodic table is starting to interact with other sciences and reports of periodic tables of amino acids (3), genetic codes (4), protein structures (5), and biology (6) can be found in the specialized literature. Symbiosis between science and art, for example, “The Periodic Table of The Elephants” (7), can also be seen. To appeal to a better understanding of the periodic table, the Instituto Superior de Engenharia do Instituto Politécnico do Porto and the Centro de Química da Universidade do Porto promoted a contest and exhibit with the goal of stimulating a wide and heterogeneous audience, ranging from young children and their parents to graduate students from several disciplines, to explore the nature of this icon. Imaginative educational activities such as contests (8–10), games (11, 12), and puzzles (13–15) provided a way to communicate with the general public with the goal of attracting students to science. This also constituted an interesting, informative, and entertaining alternative to non-interactive lectures. Simultaneously, artistic creativity was combined with scientific knowledge.